Visualising the Catalogues of Digital Editions - Bridgette Wessels; James O'Sullivan; Michael Kurzmeier; Mike Pidd; Orla Murphy (Journal of Electronic Publishing, 2024)
This article provides a data-driven overview of the developments in the field of digital scholarly editing. It surveys and evaluates the available data source on digital scholarly editions and provides longitudinal analysis of changes in number of projects, geographic distribution, licensing, interfaces and preservation. Digital scholarly editions (DSE) are essential to arts and humanities research, but also, society and culture at large. They are the primary instrument through which textual and cultural heritage, expert knowledge, and public understanding are negotiated. Their comparatively long history makes them especially suited for a diachronic approach, describing their change over time. While digital editions can vary greatly in scope and lifespan, a quantitative analysis of two of the most comprehensive data sources on digital editions can produce data-based insight into the developments within the field over time.  Exploring this history and at the same time assessing the available metadata on DSEs is the aim of this article. It presents the state of the two most comprehensive available sources on digital editions and details the methodology and visualisation process undertaken. In its analysis, it is at the same time a quantitative approach to DSEs as well as a critique of the available data sources on editions.